Evaluation of external noise produced by vehicles crossing over centerline rumble strips on undivided highways in Kansas - Makarla, Rohit (Kansas State University, 2009)
Centerline rumble strips (CLRS) are raised or indented patterns installed in the center of undivided rural two-lane highways. Their main function is to alert drivers who are encroaching or leaving the intended travel lane, by producing vibration and noise when crossed by vehicles’ tires. CLRS have been demonstrated to be an effective way in reducing head on and opposite direction sideswipe on two-lane highways (cross-over accidents). However, there are some disadvantages in their utilization, such as the exterior noise created by the strips, which may disturb residents in the highway vicinity. The objective of this study was to verify if the amount of noise created by CLRS is enough to impact negatively on residences and businesses, and to discover if the mean level of noise created by CLRS is statistically different than the noise generated by vehicles driving over smooth pavement. Two types of vehicles were driven over two different patterns of milled-in CLRS (rectangular and football-shaped) and over smooth asphalt pavement, at two different speeds. Researchers collected the noise levels at three distances 50, 100, and 150 feet, measured orthogonally from the center line, in 8 different open space locations. Results indicate that vehicle type, vehicle speed, pavement type, location and distances affect the levels of noise. In addition, both football and rectangular CLRS produced significantly higher levels of noise as compared to the smooth asphalt pavement. A 15 passenger van produced higher levels of noise in comparison with a sedan. Moreover, lower the vehicle speed, noise levels were lower. At every 50 feet of distance, the noise levels dropped significantly. CLRS do increase levels of noise relative to smooth pavement at distances up to 150 feet.
Keywords: centerline rumble strips; exterior noise; Engineering, Industrial (0546); Transportation (0709)